In Vitro Efficacy of Extracts and Isolated Bioactive Compounds from Ascomycota Fungi in the Treatment of Colorectal Cancer: A Systematic Review - Cristina Luque; Ana Cepero; Gloria Perazzoli; Cristina Mesas; Francisco Quiñonero; Laura Cabeza; Jose Prados; Consolación Melguizo (MDPI AG, 2022)
Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide. Despite the advances and success of current treatments (e.g., chemotherapy), there are multiple serious side effects which require the development of new treatment strategies. In recent years, fungi have gained considerable attention as a source of extracts and bioactive compounds with antitumor capabilities because of their antimicrobial and antioxidant properties and even their anti-inflammatory and antiviral activities. In the present review, a systematic search of the existing literature in four electronic databases was carried out in which the antitumor activity against CRC cells of Ascomycota fungi extracts or compounds was tested. The systematical research in the four databases resulted in a total of 883 articles. After applying exclusion and inclusion criteria, a total of 75 articles were finally studied. The order Eurotiales was the most studied (46% of the articles), and the ethyl acetate extraction was the most used method (49% of the papers). Penicillium extracts and gliotoxin and acetylgliotoxin G bioactive compounds showed the highest cytotoxic activity. This review also focuses on the action mechanisms of the extracts and bioactive compounds of fungi against CRC, which were mediated by apoptosis induction and the arrest of the cell cycle, which induces a notable reduction in the CRC cell proliferation capacity, and by the reduction in cell migration that limits their ability to produce metastasis. Thus, the ability of fungi to induce the death of cancer cells through different mechanisms may be the basis for the development of new therapies that improve the current results, especially in the more advanced stages of the CCR.